Differential dietary intake and contribution of ultra-processed foods during pregnancy according to nutritional status - Granich-Armenta, Adriana; Contreras-Manzano, Alejandra; Cantoral, Alejandra; Christensen, Dirk L.; Marrón-Ponce, Joaquín A.; Ávila-Jímenez, Laura; Ramírez-Silva, Ivonne; Rivera Dommarco, Juan A.; Grunnet, Louise G.; Bygbjerg, Ib C.; Lamadrid-Figueroa, Héctor (Frontiers in Nutrition, 2024)
Frequent consumption of ultra-processed foods (UPF) during pregnancy is linked to excess intake of added sugar, fat, and sodium, and inadequacy of several micronutrients. Diet quality during pregnancy should be maximized as inadequate levels of key nutrients and excessive intake of energy and added sugar may influence mother-child health. We aimed to estimate the contribution (% of total calories) of ultra-processed products to the total energy intake by pre-gestational BMI categories and Hb status during pregnancy in participants from the MAS-Lactancia Cohort. Pre-gestational weight, hemoglobin levels, 24-hour dietary intake recall interviews, and sociodemographic data were collected during the second and third trimesters of pregnancy. Reported consumed foods were categorized using the NOVA classification, and the contribution of calories from each NOVA category was estimated using the Mexican Food Database. We estimated medians and interquartile ranges (p25, p75) for dietary intake and energy contributions. The comparison of intake between the second and third trimester used the Wilcoxon test. Also, a quantile regression model with an interaction between pre-gestational BMI and Hb levels status in tertiles over the percentage of energy from UPF was adjusted by age and socioeconomic status. The contribution to total energy intake from UPF was 27.4% in the second trimester and 27% in the third trimester (with no statistical difference). The percentage of energy intake from UPF was higher in women who started pregnancy with obesity and presented the lowest levels of Hb (1 st tertile), 23.1%, 35.8% and 44.7% for the 25 th , 50 th and 75 th percentiles, respectively; compared to those with normal BMI and the highest tertile of Hb levels: 18%, 29.0 and 38.6%, for the 25 th , 50 th and 75 th percentiles, respectively. In conclusion, UPF intake in pregnant women is similar to the general population and was higher for those with pre-gestational obesity and the lowest tertile of Hb levels. UPF contributes also to sugar, saturated fat, and sodium, which may adversely affect the health of mothers and their offspring.